Body water status and short-term maximal power output during a multistage road bicycle race (Giro d`Italia 2014) - Pollastri, L.; Lanfranconi, F.; Tredici, G.; Burtscher, M.; Gatterer, H. (International Journal of Sports Medicine, 2016)
An investigation of whether body water changes during the Giro d`Italia affected average maximal mean power (MMP) of different time durations and to establish whether phase-angle and body cell mass (BCM) are related to MMP in elite cyclists. Approximately 2 h after each stage of the race, a bioelectrical impedance analysis was performed on 8 cyclists and analysed according to bioelectrical impedance vector analyses. Additionally, MMP of different time durations were recorded during each stage. Body mass increased (p<0.001), vector-length shortened (p<0.001) and MMP15 (maximal mean power for 15?s; p=0.043) decreased in the course of the Giro d`Italia. The shortening of the vector was negatively related to MMP10 (r=- 0.749, p=0.032) and MMP15 (r=- 0.735, p=0.038) during stage 16 (heavy mountain-stage) and MMP60 (r=- 0.751, p=0.032), MMP300 (r=- 0.739, p=0.036) and MMP1800 (r=- 0.769, p=0.026) during stage 19 (time-trial). Additionally, the baseline phase-angle and BCM were associated to MMP15 best (r=0.781, p=0.022 and 0.756, p=0.030, respectively). In the course of the Giro d`Italia, MMP15 decreased, indicating progressive fatigue. The vector-length shortening and to some extent the body mass increase indicate that cyclists gained body water during the race. This gain was positively associated with performance during the last stages, possibly due to improved thermoregulation. Furthermore, phase-angle and BCM, shown to be linked to cellular function and to represent metabolic active tissue, reflect individual MMP of short duration in professional road cyclists.